Issues of innovation in education - Abdullah, Syamsiah; Kamarudin, Nurzatulshima (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
The rapid development of technology has opened up new opportunities for improving the education system, to equip students with skills and attitudes to compete with the rate of innovations through the knowledge of sciences and mathematics. In Malaysia, towards the mission of 2020, the government has provided and spend large sums of money in research to improve the educational system in schools, colleges and universities to take care that no child is left behind. The transformation on entire education system such as revise the curriculum has been made in order to prepare and develop students’ skills needed for the 21st century. This points out that some strategies have been suggested to achieve the targets of meeting the 21st century challenge in producing researchers who are creative and innovative. This article describes some issues of innovation in education are raised to direct further considerations by various stakeholder especially the teachers and education stakeholders in preparing our students with critical thinking and creative in innovation.